2022
DOI: 10.31635/ccschem.021.202000740
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Engineering Active Sites at the Surface of Porous Single-Crystalline Oxide Monoliths to Enhance Catalytic Activity and Stability

Abstract: Identifying and engineering active sites play a key role in many catalytic reactions. Here we create welldefined surface structures through the growth of porous single-crystalline Mn 3 O 4 and Mn 2 O 3 monoliths at centimeter scale and confine atomically dispersed Pt ions in lattice at the twisted surface to construct isolated active sites. The activation of lattice oxygen linked to isolated Pt ions is much more effective in contrast to the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…We begin with the growth of the mother phase of AlF 3 single crystals, cut them into substrates and then treat them in O 2 /Ar atmosphere to grow PSC α‐Al 2 O 3 monolith at 500–700 Torr at 1000–1100 °C [7] . The contamination of transition metal could be negligible.…”
Section: Resultsmentioning
confidence: 99%
“…We begin with the growth of the mother phase of AlF 3 single crystals, cut them into substrates and then treat them in O 2 /Ar atmosphere to grow PSC α‐Al 2 O 3 monolith at 500–700 Torr at 1000–1100 °C [7] . The contamination of transition metal could be negligible.…”
Section: Resultsmentioning
confidence: 99%
“…The single-crystalline skeletons with diameter at the nanoscale significantly reduce the formation of defects that produces recombination centers and results in the scattering of electrons/holes within the materials. The porous architectures not only reduce light scattering to enhance light absorption but also increase the effectiveness of charge utilization by providing sufficient accessible surface areas in the three-dimensional percolation architectures. …”
Section: Functionalities and Applicationsmentioning
confidence: 99%
“…9 In addition, it has been reported that platinum ions of atomic size are dispersed in the lattice on the twisted surface of Mn 2 O 3 and Mn 3 O 4 to construct isolated active sites, so as to achieve the effect of single-atom catalysis, and oxidized CO at 65 °C. 10 However, due to the high price of these noble metal catalysts, researchers have begun to use relatively cheap transition metal substitutes, such as metal oxides, spinels, perovskites, Hopcalite and alloys. Siderite is the most widely used commercial catalyst.…”
Section: Introductionmentioning
confidence: 99%